Morphometric Description of Polistes tepidus from Ternate Island and Obi Island (Wallacea, Indonesia) - Bintoro, Wahyu Agung; Nugroho, Hari; Purwatiningsih (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to descriptively compare the morphometric measurements of two Polistes tepidus specimens from Ternate Island and Obi Island preserved in the Museum Zoologicum Bogoriense. The research was conducted by measuring morphometric characters using a Leica Z6 APO microscope and L.A.S. 4.13 software. The observed characters included the head, thorax, wings, and metasoma, which were measured from three viewing angles: frontal, lateral, and dorsal. A total of 33 morphometric characters of the paper wasp were examined, and the mean measurements were analyzed using Microsoft Excel. The results showed that the morphometric measurements of P. tepidus from the two different locations, Ternate Island and Obi Island, exhibited size variation in several body characters. In general, P. tepidus individuals from Ternate Island had larger body sizes than those from Obi Island for most morphometric characters. Habitats with abundant food resources may allow individuals to develop larger body sizes. The morphometric differences between P. tepidus from Ternate and Obi Islands may also be explained by the effects of geographic isolation and the differing ecological conditions of the two islands. The islands of the Wallacea region are known for their high environmental heterogeneity, and insect populations therefore often exhibit morphological differences among regions. These findings highlight the need for broader sampling to further test geographic differentiation.